Routledge handbook of risk, crisis, and disaster communication - Liu, Brooke Fisher; Mehta, Amisha M. (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This Handbook provides a comprehensive overview of core concepts, research, and practice in risk, crisis, and disaster communication. With contributions from leading academic experts and practitioners from diverse disciplinary backgrounds including communication, disaster, and health, this Handbook offers a valuable synthesis of current knowledge and future directions for the field. It is divided into four parts. Part One begins with an introduction to foundational theories and pedagogies for risk and crisis communication. Part Two elucidates knowledge and gaps in communicating about climate and weather, focusing on community and corporate positions and considering text and visual communication with examples from the US and Australia. Part Three provides insights on communicating ongoing and novel risks, crises, and disasters from US and European perspectives, which cover how to define new risks and translate theories and methodologies so that their study can support important ongoing research and practice. Part Four delves into communicating with diverse publics and audiences with authors examining community, first responder, and employee perspectives within developed and developing countries to enhance our understanding and inspire ongoing research that is contextual, nuanced, and impactful. Offering innovative insights into ongoing and new topics, this handbook explores how the field of risk, crisis, and disaster communications can benefit from theory, technology, and practice. It will be of interest to students, researchers, and practitioners in the fields of disaster, emergency management, communication, geography, public policy, sociology, and other related interdisciplinary fields"--
Keywords: Emergency communication; Emergency communication systems; Risk management; SCIENCE / Earth Sciences / Geography; SOCIAL SCIENCE / Human Geography